(untitled) (TAJ: Journal of Teachers Association, 2010)
Colorectal carcinoma is one of the major cancers in the developed world. It is not uniformly distributed through out the large bowel. Recent studies of patients with colorectal cancer have suggested a shift towards the proximal colon and an increase in incidence of right sided colon cancer. This study aimed to determine the anatomical distribution of colorectal in our tertiary level hospital. A total of 102 patients were selected retrospectively from Department of Gastroenterology in Rajshahi Medical College. Records of patients of colorectal cancer were reviewed for demographic data, histological type and anatomical location of tumour. Tumour located at or proximal to splenic flexure were defined as right sided cancer and tumour arising distal to the splenic flexure were defined as left sided cancer. Out of 102 patients, 74 are male and 28 are female and male: female ratio 2.6:1. The age range was from 21 to 71years with mean 46.5±13.3. Approximately seventy eight percent of cancer was left sided and 21% were right sided. Age and sex related distribution of proximal and distal tumors were analyzed but no statistically significant relation has been observed. So it is observed that the anatomical distribution of colorectal cancer has been fairly constant with no evidence of proximal shift of colorectal cancer. However multicenter large volume studies can bring a concrete opinion. TAJ 2010; 23(1): 22-25